2016
DOI: 10.3390/met6100240
|View full text |Cite
|
Sign up to set email alerts
|

Short-to-Medium-Range Order and Atomic Packing in Zr48Cu36Ag8Al8 Bulk Metallic Glass

Abstract: Due to its excellent glass-forming ability (GFA), the Zr 48 Cu 36 Al 8 Ag 8 bulk metallic glass (BMG) is of great importance in glass transition investigations and new materials development. However, due to the lack of detailed structural information, the local structure and atomic packing of this alloy is still unknown. In this work, synchrotron measurement and reverse Monte Carlo simulation are performed on the atomic configuration of a Zr-based bulk metallic glass. The local structure is characterized in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…1431 bağlı çiftlerinin sayısı sıcaklığın azalmasıyla birlikte azalırken 1541 ve özelliklede 1551 bağlı çiftlerinin sayıları keskin bir şekilde artmış (2450 K'de ~%18.12'den ve 300 K'de ~%31. 25 [29] deneyden elde ettikleri sonuçları Ters Monte Carlo yöntemi kullanarak analiz ettikleri sonuçlarla büyük oranda uyumludur. Diğer yandan bcc-tiplerin toplamı azalan sıcaklıkla neredeyse değişmezken, fcc-tiplerin toplamı azalmış ve son olarak diğer-tiplerin toplamının hızla azaldığı gözlenmiştir.…”
Section: Bulgularunclassified
“…1431 bağlı çiftlerinin sayısı sıcaklığın azalmasıyla birlikte azalırken 1541 ve özelliklede 1551 bağlı çiftlerinin sayıları keskin bir şekilde artmış (2450 K'de ~%18.12'den ve 300 K'de ~%31. 25 [29] deneyden elde ettikleri sonuçları Ters Monte Carlo yöntemi kullanarak analiz ettikleri sonuçlarla büyük oranda uyumludur. Diğer yandan bcc-tiplerin toplamı azalan sıcaklıkla neredeyse değişmezken, fcc-tiplerin toplamı azalmış ve son olarak diğer-tiplerin toplamının hızla azaldığı gözlenmiştir.…”
Section: Bulgularunclassified
“…Increased interest in BMGs over the last decades has inspired researchers to correlate local structural variations with their properties (Cheng & Ma, 2011). Many microscopy, diffraction, and simulation studies have confirmed the presence of various types of both short-range order and medium-range order (MRO) within their structure (Van Steenberge et al, 2008;Van Steenberge, 2009;Wu et al, 2014;Xu et al, 2016;Khan et al, 2018). Differential scanning calorimetry and synchrotron x-ray diffraction have also provided useful insights into the structural properties of BMGs (Qu et al, 2013;Evenson et al, 2014;Stolpe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The icosahedra are the most densest and stable packing in metallic glasses, and its fraction rapidly increases in the supercooled liquid region during cooling [9]. The icosahedra are incompatible with the long-range translational order, which presents a barrier to crystallisation and improves the glassy formability [10,11]. It has been observed in a variety of metallic glasses by molecular dynamics (MD) simulations [1216] and its fraction can be an indicator of glass formation ability (GFA) [17].…”
Section: Introductionmentioning
confidence: 99%